Correlation of Ultra-processed Food Consumption with Nutritional Status and Blood Pressure in Adolescents - Khuzaimah, Anna; Indriyani Prima Ruttu; Nurhaedar Jafar (Window of Health : Jurnal Kesehatan, 2025)
Adolescents are nutritionally vulnerable, and their intake is crucial to avoid nutritional problems during growth. Adolescent food consumption can be obtained from various types of food, one of them ultra-processed food (UPF). This study aims to determine the relationship between ultra-processed food consumption patterns and nutritional status and blood pressure in Catholic Junior High School Sudiang adolescents and Christian Elim High School Makassar. Methods: This study is a quantitative descriptive study with a cross-sectional design. The sample was selected using a proportional random sampling technique of 195 adolescents aged 13-18. UPF consumption was collected using the Semi Quantitative Food Frequency Questionnaire (SQ-FFQ). The research results show adolescents are overweight at 25.6% and obese at 21%; elevated blood pressure (BP) is 14.4%, and state hypertension (HTN) is 8.2%. In addition, obese adolescents with state 1 HTN were 17.1% and elevated BP by 24.4%, while overweight adolescents with state 1 HTN were 8% and elevated BP by 14%. There is a correlation between the amount of UPF consumption and nutritional status (p-value = 0.047). At the same time, the results were negative between the frequency of UPF consumption and nutritional status (p-value = 0.312), the amount of UPF consumption and BP (p-value = 0.289), and the frequency of UPF consumption and BP (p-value = 0.059). The study concludes a significant correlation between the amount of ultra-processed food consumption and nutritional status in adolescents. Further research and public health interventions are recommended to address the impact of UPF on adolescent health.